2011
DOI: 10.1136/ard.2010.144451
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal antibody levels after pneumovax in patients with rheumatoid arthritis on methotrexate

Abstract: This study suggests that a single administration of pneumovax early in RA offers up to 10 years protection against the development of pneumococcal pneumonia in RA patients on methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 24 publications
3
32
0
8
Order By: Relevance
“…In contrast, a study by Elkayam et al 17 did not demonstrate a detrimental effect of immunosuppressive drugs such as MTX on PPV23 immunogenicity in RA patients. Coulson et al 18 have also suggested that a single PPV23 administration offers up to 10 years of protection against the development of pneumococcal pneumonia in RA patients receiving MTX therapy. Determining serotype-specific IgG concentrations after PPV23 vaccination in patients receiving MTX therapy is recommended 19…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study by Elkayam et al 17 did not demonstrate a detrimental effect of immunosuppressive drugs such as MTX on PPV23 immunogenicity in RA patients. Coulson et al 18 have also suggested that a single PPV23 administration offers up to 10 years of protection against the development of pneumococcal pneumonia in RA patients receiving MTX therapy. Determining serotype-specific IgG concentrations after PPV23 vaccination in patients receiving MTX therapy is recommended 19…”
Section: Discussionmentioning
confidence: 99%
“…101 Compared with healthy individuals, for patients with RA, similar 61,63,102,103 as well as lower [103][104][105][106] humoral responses to pneumococcal vaccine have been shown, depending on the medication used.…”
Section: Hib and Pneumococcal Vaccinesmentioning
confidence: 97%
“…было показано, что однократное введение ППВ23 в дебюте ревмато-идного артрита до назначения терапии обеспечивает защиту против пневмококковой пневмонии в течение 10 лет у пациентов с ЮИА на фоне терапии метотрек-сатом [24].…”
Section: актуальностьunclassified